Nudging, formulating new products, and the lifecourse: A qualitative assessment of the viability of three methods for reducing Scottish meat consumption for health, ethical, and environmental reasons. (1st November 2019) - McBey, David; Watts, David; Johnstone, Alexandra M.
Abstract: Most governmental initiatives designed to improve dietary and planetary health have adopted a light-touch informing approach. However, it may be necessary to consider more direct measures that go beyond simply informing the public if the current high levels of meat consumption in Scotland are to be addressed. This paper considers three possible avenues through which more sustainable meat consumption patterns may be promoted: 'nudging', the formulation of new meat-alternative products, and targeting those in particular stages of the lifecourse. Through focus groups held in various locations in Scotland, the perceived viability of these measures was explored. While each measure shows some promise for reducing Scottish meat intake, the complex nature of food choice means that more qualitative research into meat consumption in Scotland is required.